The frequency of enamel and dentin caries lesions among elderly Norwegians. (2nd January 2020) - Mulic, Aida; Tveit, Anne B.; Stenhagen, Kjersti Refsholt; Oscarson, Nils; Staxrud, Frode; Jönsson, Birgitta
Abstract: Aim: To describe the distribution of enamel-, dentin-, root- and secondary caries within an elderly population in Northern-Norway. Material and methods: A study population ( n = 1 173) was divided into age groups: 65–69 (seniors), 70–74 (young elderly), 75–79 (elderly) and 80–94 (old elderly). Seven examiners registered presence, location and severity of caries lesions on x-rays and intra-oral photos. Severity of approximal, occlusal, secondary and root caries was graded (D1–2 : into enamel; D3–5 : into dentin, root caries), and decayed missing filled surfaces/teeth (DMFS/DMFT) were calculated. T-test, ANOVA and a Bonferroni correction were used. Results: The seniors had more primary caries (DS1–5 ) compared to the oldest age groups, while the old elderly had significantly more secondary caries than the other groups ( p < .05). Of those ≥65 years 13.8% were affected with root caries, 21% among the oldest. About 48% of the old elderly had one or more surfaces with untreated caries lesions into dentin, while for the other groups the number was 35% ( p < 0.05). Conclusion: Individuals seem to maintain good oral health up to at least 80 years of age. Those older than 80 years have more root caries needing more intensified caries-controlling measures and a higher prevalence of untreated dentin lesions often in need of operative treatment.